Single-cell characterisation of T lymphocyte immune responses in spondyloarthropathy - Penkava, F (2019)
The spondyloarthropathies (SpA) are a collection of inflammatory disorders of undetermined etiology affecting the joints and connective tissues, however existing evidence suggests a role for the microbiome, CD4 and CD8 T cells in disease pathogenesis.